Experience with nusinersen as a pathogenetic therapy in adult patients with spinal muscular atrophy 5q in the Republic of Bashkortostan - S. V. Umutbaev; L. Sh. Murzabaeva; M. A. Kutlubaev; A. V. Shishigin; T. N. Sharipov; E. V. Sayfullina; R. V. Мagzhanov (Нервно-мышечные болезни)
Background. Spinal muscular atrophy (SMA) affects 1 in 11,000 people. Until 2016, this was considered an incurable disease, but after the approval of nusinersen, the situation has changed. The efficacy of nusinersen therapy is also known in adult patients, although research is limited due to the majority of studies in infants and children. Nusinersen has been included in the list of “Vital and Essential Medicines” since 2021.Aim. To analyze the experience of using nusinersen as a pathogenetic therapy for patients over 18 years of age with SMA 5q in the Republic of Bashkortostan.Materials and methods. We examined eight patients receiving pathogenetic therapy with nusinersen (SMA type 2 – 34.5 %, SMA type 3 – 65.5 %). The Hammersmith Functional Motor Scale Expanded (HFMSE) and the Revised Upper Limb Module (RULM) were used for evaluating the effectiveness of therapy.Results. The median increase on the HFMSE scale was +2 points (7.5, with the initial 5.5) and on the RULM scale – +4.5 points (17 points, with the initial 12.5). Clinically, this was expressed in an increase in muscle strength, an increase in daily activity; a decrease in bulbar, respiratory and vegetative disorders can also be noted. Subjectively, positive dynamics was noted in the increase in working capacity, improvement of the emotional background.Conclusion. The use of the drug nusinersen in adult patients with SMA 5q in some cases provides clinical improvement. The presence of an “overall response” is defined as clinically significant change in one assessed measure of motor function.